Inter-relações entre ensino de história e formação docente por meio da educação histórica e da construção de identidades narrativas – região sul do Brasil (2016-2020) - Rosanelli, Sandiara Daíse (2022)
The present master's dissertation refers to a research developed together with the master's degree in Education in the Postgraduate Program in Education of the Federal University of Santa Maria (PPGE/UFSM), whose objective is to carry out an analysis about the interrelationship between the Teaching History and the construction of narrative identities of subjects teaching, based on History Education, in order to understand how the concepts of History Education, History Teaching, historical consciousness, narrative and identity are linked to the training of professionals, historians-teachers. It is understood that the construction of identities is a broad, complex process of continuous development during the life of every human subject. These subject-teachers are considered a constituent part of History, so that their narrative identities are reflected in their educational practices and in their (self)formation processes. The central problem of this research is the question: How does the Teaching of History and significant educational practices in formal education build narrative identities of subjects-teachers, historians-teachers, through the use and support of History Education? The investigation methodology of this research is permeated by a theoretical, qualitative and documentary approach, guided by the current of History Education and by the meaning of narratives present in selected dissertations and theses in the field of Education and History Teaching, where, through writing, the subject-teachers present identity elements, directly and/or indirectly through the conceptual and theoretical choices they make. Thus, this research, framed in the research line "LP2 - Public educational policies, educational practices and their interfaces", from PPGE/UFSM, allows a reflection on the construction of historical culture in relation to teaching, to the work of the historian as a teacher and producer of knowledge, at the same time, which interrelates the concepts to the educational practices involved in the construction of historical and educational culture, so that the formation of the historian focused on the being-teacher, and his teaching practices, has meaning and can help in the construction of historical knowledge beyond the academy and society in which we live. The analysis of documentary sources (dissertations and theses) allowed us to understand the development of the interrelationship between History Teaching and the construction of narrative identities of subject-teachers, through the meaning of teaching and learning in a way connected with research and theory, as well as with the formation of the subject and historical knowledge. The meaning of the teaching-learning process, interconnected with the teaching and identity formation of the subjects, also makes it possible to qualify the Teaching of History and bring it closer to reality, especially through the meaning of the historical past from the present, with perspectives of the future, of so that this process makes sense for all the subjects involved.